2013
DOI: 10.1083/jcb.201304051
|View full text |Cite
|
Sign up to set email alerts
|

Lamellipodin and the Scar/WAVE complex cooperate to promote cell migration in vivo

Abstract: Lpd is an essential, evolutionary conserved regulator of the Scar/WAVE complex during cell migration in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
172
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(193 citation statements)
references
References 55 publications
(113 reference statements)
16
172
0
1
Order By: Relevance
“…These results are consistent with previous reports that HGF/c-Met signalling promoted cell migration through lamellipodia and filopodia formation in lung endothelial cells (28) and in some normal cells (30). Thus, it is possible that lamellipodia and filopodia formation is regulated by c-Met signalling, thereby promoting the migration of OSCC cells.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…These results are consistent with previous reports that HGF/c-Met signalling promoted cell migration through lamellipodia and filopodia formation in lung endothelial cells (28) and in some normal cells (30). Thus, it is possible that lamellipodia and filopodia formation is regulated by c-Met signalling, thereby promoting the migration of OSCC cells.…”
Section: Discussionsupporting
confidence: 82%
“…In this context, we showed that c-Met signalling was involved in the regulation of lamellipodin protein levels. Promotion of cell migration potency via the c-Met pathway is possibly regulated by increasing the level of lamellipodin, because upregulation of lamellipodin protein markedly promoted cell migration (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lpd is an actin-remodeling protein reported to bind PI(3,4)P2 (30) and to regulate random motility in nonhematopoietic cells (34). To determine whether Lpd may be a mediator of PI(3,4)P2-dependent chemotaxis in malignant B cells, we first examined expression of Lpd in human B cells and found that Lpd is expressed in a variety of malignant B cell lines and primary CLL B cells (Fig.…”
Section: Lpd Is Expressed In Malignant B Cells and Colocalizes With Pmentioning
confidence: 99%
“…Lpd was shown to mediate random motility in breast cancer cells (29,34) as well as extension of neuronal processes (35). It remains unknown whether Lpd is involved in directional migration in response to specific chemotactic stimuli, and whether the function of Lpd in promoting cell migration depends on its PI(3,4)P2-binding PH domain.…”
mentioning
confidence: 99%